FGFR3 deficiency enhances CXCL12-dependent chemotaxis of macrophages via upregulating CXCR7 and aggravates joint destruction in mice. Issue 1 (29th October 2019) - Kuang, Liang; Wu, Jiangyi; Su, Nan; Qi, Huabing; Chen, Hangang; Zhou, Siru; Xiong, Yan; Du, Xiaolan; Tan, Qiaoyan; Yang, Jing; Jin, Min; Luo, Fengtao; et al.
Abstract : Objectives: This study aims to investigate the role and mechanism of FGFR3 in macrophages and their biological effects on the pathology of arthritis. Methods: Mice with conditional knockout of FGFR3 in myeloid cells (R3cKO) were generated. Gait behaviours of the mice were monitored at different ages. Spontaneous synovial joint destruction was evaluated by digital radiographic imaging and μCT analysis; changes of articular cartilage and synovitis were determined by histological analysis. The recruitment of macrophages in the synovium was examined by immunostaining and monocyte trafficking assay. RNA-seq analysis, Western blotting and chemotaxis experiment were performed on control and FGFR3-deficient macrophages. The peripheral blood from non-osteoarthritis (OA) donors and patients with OA were analysed. Mice were treated with neutralising antibody against CXCR7 to investigate the role of CXCR7 in arthritis. Results: R3cKO mice but not control mice developed spontaneous cartilage destruction in multiple synovial joints at the age of 13 months. Moreover, the synovitis and macrophage accumulation were observed in the joints of 9-month-old R3cKO mice when the articular cartilage was not grossly destructed. FGFR3 deficiency in myeloid cells also aggravated joint destruction in DMM mouse model. Mechanically, FGFR3 deficiency promoted macrophage chemotaxis partly through activation of NF-κB/CXCR7 pathway. Inhibition of CXCR7 could significantly reverse FGFR3-deficiency-enhanced macrophage chemotaxis and the arthritic phenotype in R3cKO mice. Conclusions: Our study identifies the role of FGFR3 in synovial macrophage recruitment and synovitis, which provides a new insight into the pathological mechanisms of inflammation-related arthritis.